The media text of a musical work and its medium texts - Katrych, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of the study is due to the modern expectations of music science regarding the adequate reflection in its conceptual and terminological apparatus of the media reality of musical phenomena of the modern era. The key in this sense is the phenomenon of a musical work in the aspect of understanding its ontology as a media text. The phenomenon of the media text of a musical work is considered in the genetic interconnection with its medium texts. Theoretical base. The analytical basis of the reasoning presented in the scientific research is the work of the Ukrainian scientist-musicologist, the founder of the Ukrainian school of musical interpretation, Viktor Moskalenko. The achievements of the modern philosophical and sociological discourse, in particular, individual provisions of the works of Michel Foucault, Michel Maffesoli, Jacques Lacan, Jorjio Agamben, etc., own scientific positions and materials of musical-empirical experience structured on the basis of musical-performance practice of outstanding musicians became the essential basis of theoretical generalizations. - interpreters of the beginning of the 20th century 21st century The complex scientific methodology applied in scientific research, which combines the methods of empirical observations of the compositional and performance practice of musical activity, discourse analysis, comparative studies and musicological theoretical generalizations, deepens the understanding of the mechanisms of musical creativity in the plane of the media ontology of a musical work, which allows achieving the main objectives of substantiating the semantic content and concretizing analytical resource of concepts of media text and medium text of a musical work. The scientific novelty of the presented considerations is determined by the introduction into scientific circulation and the definitional specification of the concepts of media text and medium text of a musical work. The conclusion summarizes the results of the research, points out the perspective of the musicological examination of musical phenomena in the aspect of their media ontology, and substantiates the concepts of media text and the medium text of a musical work. The conducted research opens perspectives for the further development of musical media discourse and understanding of musical phenomena taking into account their modern noumenal media specificity